A reanalysis of fatigue test data for longitudinal welded gusset joints in as-welded and high frequency mechanical impact (HFMI)-treated state. (August 2021) - Ono, Yuki; Baptista, Claudio; Kinoshita, Koji; Yıldırım, Halid Can; Nussbaumer, Alain
Highlights: Reanalyzed database considering specimen geometry, loading, R -ratio, HFMI, etc. Confirmed gradings of fatigue strength improvement effect of HFMI proposed by IIW. Combined effects of gusset length, main plate width and thickness. New relationship proposed that considers combined effects for as-welded and HFMI. Proposed modified FAT categorization for Eurocode 3 and IIW in case of HFMI. Abstract: This study aims at clarifying the combined effect of different geometric parameters on the fatigue strength of longitudinal welded gusset joints. Statistical reanalyses with an up-to-date database for this detail were thus carried out on larger parameter ranges, first on as-welded joints, including also loading, weld detailing, steel grade, and R -ratio. The results showed that the combined effect of gusset length, main plate width and thickness significantly affects the characteristic values and a relationship is proposed. With this basis, analyses are then performed on high frequency mechanical impact (HFMI)-treated joints and an accurate assessment of the improvement effect is proposed.